Feeling Gender A Generational and Psychosocial Approach - Nielsen, Harriet Bjerrum (Palgrave Macmillan Studies in Family and Intimate Life, 2017)
This book explores how feelings about gender have changed over three interrelated generations of women and men of different social classes during the twentieth century. The author explores the ways in which generational experiences are connected, what is continued, what triggers gradual or abrupt changes between generations - and between women and men within these generations. The book explores how new feelings of gender gradually change gender norms from within, and how they contribute to the incremental creation of new social practices. Nielsen suggests a new way of conducting psychosocial research that focuses on generational psychological patterns of gender identities and gendered subjectivities in times of change from a psychoanalytic perspective. Combining generational and longitudinal research, the book works with temporality as a theoretical as well as a methodological dimension. Theoretically it combines Raymond Williams' idea of "a structure of feeling" with thework of Eric Fromm, Hans Loewald, Nancy Chodorow and Jessica Benjamin.